Idiopathic congenital Horner Syndrome. Presentation of a case - Leopoldo Garduño-Vieyra; Raul Rua Martinez; Natalia Rodriguez Mena; Isabel De la Fuente Batta (Ukrainian Society of Ophthalmologists, 2023)
Horner Syndrome results from an interruption of the sympathetic innervation of the eye. This pathway is a chain of three neurons which originate in the hypothalamus, travels down to spinal cord at the level of lower cervical and upper thoracic levels, then traverses the upper chest cavity traveling with the carotid artery, traverse the orbit to innervate pupillary sphincter and accessory muscles for eyelid retraction. The classic clinical triad is unilateral ptosis, miosis and anhidrosis. There are many causes of Horner Syndrome which can be congenital o acquired. During the first year of life is most often idiopathic in 70%, but the others can be related to neuroblastoma, that's why it is so important to recognize the cause of the syndrome in each patient. In this paper we describe a case report of congenital Horner syndrome, how the diagnosis was made, identification of the causing injury and differential diagnosis.